A Case of Methylmercury Poisoning - Wunder, Meaghan; Bhati, Piali (Western Libraries, 2022)
Since the early 1960’s the Asubpeeschoseewagong Netum Anishinabek in Northern Ontario have been living with the consequences of chronic methylmercury poisoning. From 1962 to 1970, mercury waste was dumped into the English-Wabigoon river upstream from Grassy Narrows First Nation, contaminating the water and the fish within. In 1970, inappropriate mercury disposal was ceased, commercial fishing was prohibited, and individuals were advised not to consume fish from the river. These restrictions and their consequences profoundly affected the economic, cultural and medical wellbeing of the Asubpeechoseewagong people. Methylmercury poisoning, coined Minamata disease in Japan, has been one medical consequence of this pollution. Minamata disease describes irreversible damage to the central nervous system as a result of methylmercury poisoning, including lesions in the cerebellum, anterior calcarine cortex, and surrounding the central sulcus. Individuals commonly experience somatosensory disturbances and distal paresthesia, cerebellar ataxia and dysarthria, and visual field constriction. This case report will describe a young Asubpeechoseewagong person suffering the early consequences of methylmercury poisoning. Subsequently, the history of Minamata disease in Ontario, the pathophysiology of methylmercury poisoning, and investigations and management will be discussed. It is important to note that the story of this case is not a historical perspective. The Grassy Narrows First Nation continue to live with the results of this profound environmental injustice. In the words of Chief Simon Fobister, “we must not deny another generation of our children a bright future by refusing to clean our river.”